Functional and stylistic features of neologisms in the Ukrainian-language segment of the social network "Twitter" - Козка, Давид Віталійович (Київський національний університет імені Тараса Шевченка, 2024)
The article outlines and analyzes the functional and stylistic parameters of neologisms in the Ukrainian-language segment of the social network "Twitter". The research data is based on more than two thousand Ukrainian-language Twitter posts in 2020-2024. Given the specifics of network, whose main purposes of which are providing communication and information, the following functions of neologisms in tweets are distinguished: nominative, communicative, attention- grabbing, influence-related, and pragmatic. The nominative function of the named words in tweets realizes the need to give new realities, individuals, phenomena, and events names that do not yet exist either in general usage or in lexicographical works. Neologisms also serve as a means of self-nomination and are part of aphorisms and paraphrases. The structure of tweets that represent the attention-grabbing function includes marker lexemes, with the help of which the author encourages online communicators to pay attention to a certain event, phenomenon, situation, or give their own assessment of it. Neologisms are used in interrogative statements, prompting communicators to hold their attention on posts, reflect on the information presented in them, and sometimes take the position of the tweet author in a reply. The cognitive function of neologisms is to verbalize the ability of the author of a tweet to understand, perceive, and learn information, i.e. to activate the author's speech and nominative activity with his or her pragmatic instructions. The analysis of the factual material suggests that since tweets are representatives of the author's views, and value judgments regarding certain events, concepts, and phenomena, it is advisable to distinguish the pragmatic function of neologisms in tweet expressions. The use of neologisms in tweets is influenced by pragmatic factors that reflect the author's attitude to the message; pragmatic information in tweets is expressed in evaluative neolexemes derived in different ways and represented mainly by noun and adjectival formations. The article focuses on analyzes neologisms with the morpheme ze-, which has recently become a productive class of neologisms.

У статті окреслено й проаналізовано функційно-стилістичні параметри неологізмів в українськомовному сегменті соціальної мережі"Твіттер". Матеріалом дослідження слугували понад дві тисячі українськомовних дописів у соціальній мережі "Твіттер" за 2020 – 2024 роки. З огляду на специфіку спілкування в мережі, основним призначенням якої є комунікація та інформація, виокремлено такі функції неологізмів у твітах: номінативну, комунікативну, привернення уваги, впливу, прагматичну. Номінативна функція названих слів у твітах зреалізовує необхідність надавати новим реаліям, особам, явищам, подіям назви, яких ще не існує ні в широкому вжитку загалом, ні в лексикографічних працях. Неологізми також слугують засобом самономінації та входять до складу афоризмів-перифразувань. До структури твітів, що репрезентують функцію привернення уваги, входять лексеми-маркери, із допомогою яких автор спонукає інтернет-комунікантів звернути увагу на певну подію, явище, ситуацію чи на власну їх оцінку. Неолексеми залучають до складу питальних конструкцій, спонукаючи комунікантів затримати увагу на дописах, поміркувати над інформацією, представленою в них, а подекуди сприйняти позицію автора твіту у відповіді на відписи інших користувачів. Когнітивна функція неологізмів полягає у вербалізації здатності автора твіту розуміти, сприймати, пізнавати інформацію, тобто в активізації мовленнєво-номінативної діяльності автора з його прагматичними настановами. Аналіз фактичного матеріалу дає підстави вважати, що оскільки твіти – репрезентанти поглядів, оцінних суджень щодо певних подій, понять, явищ авторів, то доцільно виокремити прагматичну функцію неологізмів у складі твітових висловлень. На використання неологізмів у твітах мають вплив прагматичні чинники, що відображають ставлення автора до повідомлюваного; прагматична інформація у текстах твітів виражена в оцінних неолексемах, деривованих різними способами та представлених здебільшого іменниковими й прикметниковими утвореннями. Проаналізовано новотвори з аброморфемою зе-, які останнім часом становлять продуктивний клас неологізмів.
Функційно-стилістичні особливості неологізмів в українськомовному сегменті соціальної мережі "Твіттер"
Keywords: neologisms; functions; stylistic features; Internet communication; Ukrainian-speaking segment; tweet; неологізми; функції; стилістичні особливості; інтернет-комунікація; українськомовний сегмент; твіт